(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Positron Emission Tomography-Computed Tomography (PET-CT) is one of the latest state-of-the-art hybrid imaging techniques of nuclear medicine that has various applications in oncology, neurology, cardiology, and infectious disease evaluation. However, accessing this facility in Bangladesh and other 3rd world countries remains limited mostly due to financial barriers. Limited infrastructure, radiopharmaceutical unavailability, and lack of skilled and trained personnel are also some major obstacles of accessing PET-CT in this country. The difficulties patients and nuclear medicine staff encounter while trying to obtain and use 18FFDG PET-CT services in a newly established institute like Institute of Nuclear Medicine and Allied Sciences (INMAS), Suhrawardy along with some scenario-based operational challenges have been highlighted in this context. Bangladesh J. Nuclear Med. 28(1): 75-80, 2025